Resource Centre or Experience Desk? The Spatiality of Services to Indigenous and International Students at Universities in Ontario, Canada - Montsion, Jean Michel (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2018)
In recent years, Ontario universities have increasingly targeted Indigenous and international students for recruitment. Focusing on three southern Ontario universities, I examine how service delivery for these student groups is organized in space. In light of Henri Lefebvre’s work, I argue that the spatiality of the information hubs created to support them differs significantly, each being defined in the interactions between institutional assumptions about the student group, the social presence and activities hosted, and the lived experiences of the students utilizing these services. Whereas Indigenous student services are organized as a resource centre to create a separate space for Indigeneity on campuses, international student services take the form of an experience desk to emphasize rapid integration into the mainstream. Based on interviews with students and staff, I reflect on the differences between the two models to discuss the spatial politics of information hubs within the context of Ontario universities.